2015 24th IEEE International Symposium on Robot and Human Interactive Communication (RO-MAN) 2015
DOI: 10.1109/roman.2015.7333656
|View full text |Cite
|
Sign up to set email alerts
|

Perceived robot capability

Abstract: Abstract-Robotics research often focuses on increasing robot capability. If end users do not perceive these increases, however, user acceptance may not improve. In this work, we explore the idea of perceived capability and how it relates to true capability, differentiating between physical and social capabilities. We present a framework that outlines their potential relationships, along with two user studies, on robot speed and speech, exploring these relationships. Our studies identify two possible consequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 30 publications
0
35
0
1
Order By: Relevance
“…While our model assumes that the human may learn only the entries of the row played by the robot, there are cases where a robot action may affect entries that are associated with other actions, as well. For instance, Cha et al [2] have shown that conversational speech can affect human perception of robot capability in physical tasks. We are excited to explore the structure of probabilistic graphical models of human adaptation, and use the theoretical insights from this work to develop efficient algorithms for the robot.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While our model assumes that the human may learn only the entries of the row played by the robot, there are cases where a robot action may affect entries that are associated with other actions, as well. For instance, Cha et al [2] have shown that conversational speech can affect human perception of robot capability in physical tasks. We are excited to explore the structure of probabilistic graphical models of human adaptation, and use the theoretical insights from this work to develop efficient algorithms for the robot.…”
Section: Resultsmentioning
confidence: 99%
“…We propose a model of human partial adaptation, where the human learns with probability α the entries of row ri that correspond to the robot action a R i played, and with probability (1 − α) none of the entries. We consider the following models, based on 2 We will use the terms 'reward' and 'payoff' interchangeably. 3 We will refer to this robot action as playing a row.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Robots can forewarn users of possible failures through text [18] or con dence levels [7,15], trajectory timings [32], and actively choosing actions that showcase failure modes [23]. Se ing accurate expectations of robot capabilities is important for narrowing the gap between the perceived and true capabilities of the robot [6].…”
Section: Related Workmentioning
confidence: 99%
“…Sciu i et al [2014], Zhou et al [2017] have developed expressive robotic lifting motions to help humans understand the weights of the objects that robots are manipulating. The ease with which a person could recognize a robot's goals by observing its action execution improves robot legibility [Dragan et al, 2013, Dragan and Srinivasa, 2014], predictability [Fisac et al, 2016, acceptance [Cha et al, 2015], and naturalness [Szafir et al, 2014], which are important for human recognition of robot tasks and human-robot collaboration [Powers andKiesler, 2006, Gielniak et al, 2013]. However, the prior works aim to make current executed behavior and goals more understandable and does not focus on helping people more easily predict future actions and generalize current behavior to new environments.…”
Section: Related Workmentioning
confidence: 99%